Purification of Antilisterial Peptide (Subtilosin A) from Novel Bacillus tequilensis FR9 and Demonstrate Their Pathogen Invasion Protection Ability Using Human Carcinoma Cell Line - Parveen Rani, Rizwana; Anandharaj, Marimuthu; Hema, Subramani; Deepika, Ramasamy; David Ravindran, Abraham (Frontiers in Microbiology, 2016)
This study focuses on isolation, screening and characterization of novel probiotics from gastrointestinal tract of free-range chicken (Gallus gallus domesticus). Fifty seven colonies were isolated and three isolates (FR4, FR9 and FR12) were selected and identified as Lactobacillus gasseri FR4, Bacillus tequilensis FR9 and L. animalis FR12 by 16S rRNA sequencing. Three strains were able to survive in stimulated acidic and bile conditions and inhibit the growth of pathogens. Especially, FR9 exhibited maximum inhibition against Listeria monocytogenes and none of them exhibited hemolytic activity. Native-PAGE revealed the presence of low molecular weight (3.4-5.0 KDa) antimicrobial peptide. The peptide was further purified by Sephadex G-50 column and RP-HPLC using C18 column. N-terminal amino acid sequencing of antimicrobial peptide showed 100% consensus to antilisterial peptide SubtilosinA and SboA gene was amplified from FR9 genome. FR9 showed maximum aggregation activity, EPS production (85.46 mg/L) and cholesterol assimilation (63.12 ± 0.05 µg/mL). Strong adhesion property (12.6%) and pathogen invasion protection ability was revealed by B. tequilensis FR9 towards HCT-116 human colon carcinoma cell line. This is the first study to demonstrate antilisterial SubtilosinA production of B. tequilensis. Our results indicate that B. tequilensis FR9 strain furnish the essential characteristics of a potential probiotics and might be incorporated into human and animal food supplements.